2021
DOI: 10.1088/1755-1315/788/1/012182
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of fishmeal with black soldier fly larvae (Hermetia illucens L) against the performance of native chickens grower phase

Abstract: Black Soldier Fly (BSF) larvae (Hermetia illucens) is a feed that has a high protein content. The research aims to determine the role of the use of the BSF larvae the performance of a grower-phase poultry that substituted fish flour. A total of 120 4-week-old native chickens were alloted to 5 dietary treatments and 4 replications based on the completely randomized design. The treatment consists of P0 (basal rations + 100% fish flour), P1 (basal rations + 75% fish flour + 25% BSF larvae flour), P2 (basal ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Murawska et al (2021) reported an improvement in FCR of broiler chickens fed 17% BSF larvae meal (BSFLM) in a 42-d experiment. Improvement in FCR occurred in broiler chickens fed diets with partial replacement of fish meal (75%) with BSFLM (Wahid et al, 2021). Replacement of dietary 2, 4, 6, and 8% fish meal with BSF maggot meal (BSFMM) in broiler chickens from 14 to 56 days improved the feed conversion ratio (FCR), increased the body weight gain (BWG), and reduced the feed intake (FI) compared to the control diet (Attivi et al, 2020).…”
Section: Effects On Growth Performancementioning
confidence: 99%
“…Murawska et al (2021) reported an improvement in FCR of broiler chickens fed 17% BSF larvae meal (BSFLM) in a 42-d experiment. Improvement in FCR occurred in broiler chickens fed diets with partial replacement of fish meal (75%) with BSFLM (Wahid et al, 2021). Replacement of dietary 2, 4, 6, and 8% fish meal with BSF maggot meal (BSFMM) in broiler chickens from 14 to 56 days improved the feed conversion ratio (FCR), increased the body weight gain (BWG), and reduced the feed intake (FI) compared to the control diet (Attivi et al, 2020).…”
Section: Effects On Growth Performancementioning
confidence: 99%
“…One of the variants coming to be exploited is the use of flour obtained from insects. The larvae of the black soldier fly (Hermetia illucens L.), a species native to America and now widespread throughout the world, can be converted into flour with a high protein content, useful in feeding fish (Meitiyani et al 2020) and birds (Wahid et al 2021).…”
Section: ¿Biodiversity Vs Bioeconomy?mentioning
confidence: 99%
“…With this advantage, BSFL is already used today as a protein substitute ingredient in the diets of monogastric animals, including poultry, pigs, and dogs [ 12 ]. Previous studies have reported that feeding BSFL as a substitute for soybean meal or fishmeal can improve the broiler feed conversion ratio (FCR) [ 13 , 14 ]. Also, insects may be processed in various ways, such as hydrolysis, defatting, and heat processing, and used in animal diet ingredients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%